Fermentation of organic solid wastes as a source of renewable energy and the use of the product as fertilizer - Yılmaz, Ayşe Hilal (Ege Üniversitesi, 1998)
Bu tezin, veri tabanı üzerinden yayınlanma izni bulunmamaktadır. Yayınlanma izni olmayan tezlerin basılı kopyalarına Üniversite kütüphaneniz aracılığıyla (TÜBESS üzerinden) erişebilirsiniz. IV ABSTRACT FERMENTATION OF ORGANIC SOLID WASTES AS A SOURCE OF RENEWABLE ENERGY AND THE USE OF THE PRODUCT AS FERTILIZER YILMAZ, Ayşe Hilal. MSc in Chemical Engineering Supervisor : Assoc. Prof. Dr. Ferhan Sami ATALAY August 1998, 75 pages In this study, methane production from different organic solid wastes was investigated using six small laboratory fermenters each having a volume of 10 liters, and a pilot plant fermenter having a volume of 0.96 m3. Results of the experiments were tested to the different microbial kinetics indicated in literature, and the best fitting model relating the specific growth rate of micro-organisms for each solid waste was determined using nonlinear regression method. Several authors have commented on the fertilizer quality of digester slurry. Unfortunately, data on the fertilizer value of the slurry from biogas plants are inadequate, because the effect of slurry from biogas plants as fertilizer requires much time, and should be studied in details. In this study, the use of the digested wastes as fertilizer could not be investigated, because of lack of time. Keywords: biogas, methane production, anaerobic fermenter, organic solid waste, nonlinear regresssion Ill ÖZET KATI ATIKLARIN FERMENTASYONUYLA YENİLENEBİLİR ENERJİ ELDESİ VE ÜRÜNÜN GÜBRE OLARAK KULLANIMI YILMAZ, Ayşe Hilal Yüksek Lisans Tezi, Kimya Mühendisliği Bölümü Tez Yöneticisi : Doç. Dr. Ferhan Sami ATALAY Ağustos 1998, 75 sayfa Bu çalışmada, her biri 10 litre hacmindeki altı adet laboratuvar fermentörü ve 0.96 m3 hacmindeki pilot fermentör kullanılarak değişik organik katı atıklardan elde edilen metan gazı üretimi incelenmiştir. Deneylerin sonuçlan literatürde bulunan değişik mikrobial kinetiğine uygulanmıştır. Sonuçta lineer olmayan regresyon metodu kullanılarak her bir organik katı atık için mikroorganizmaların özgül büyüme ...